Frequency, impact, and predictors of persistent pain after root canal treatment: a national dental PBRN study. Issue 1 (January 2016) - Nixdorf, Donald R.; Law, Alan S.; Lindquist, Kimberly; Reams, Gregory J.; Cole, Emery; Kanter, Keith; Nguyen, Ruby H.N.; Harris, D. Robert
Abstract : Abstract: Root canal treatment (RCT) is commonly performed surgery and persistent pain is known to occur, but little is known about how these patients are affected by this pain. Although biopsychosocial mechanisms are thought to be associated with the development of such pain, similar to persistent pain after surgery in other body sites, little is known about the baseline predictors for persistent pain. We assessed the frequency of persistent pain 6 months after RCT, measured the impact this pain had on patients, and determined predictive factors for persistent tooth pain in a multicenter prospective cohort study conducted within the National Dental Practice-Based Research Network. Of 708 patients enrolled, 651 (91.9%) provided follow-up data, with 65 (10.0%) meeting criteria for pain 6 months after RCT. On average, these patients reported their pain as mild to moderate in intensity, present for approximately 10 days in the preceding month, and minimally interfered with daily activities. After adjusting for the type of dental practitioner and patient age, gender, and household income, pain duration over the week before RCT significantly increased the risk of developing persistent pain (odds ratio = 1.19 per 1 day increase in pain duration, 95% confidence interval: 1.07-1.33), whereas optimism about the procedure reduced the risk (odds ratio = 0.39, 95% confidence interval: 0.22-0.67). Our data suggest that persistent pain 6 months after RCT is fairly common, but generally does not have a large impact on those experiencing it. Furthermore, patient age and gender did not predict persistent pain, whereas preoperative pain duration and the patient's expectation did. Abstract : Patient age and sex, as well as dentist training, did not predict persistent pain after root canal treatment, whereas preoperative pain duration and the patient's expectation did.Supplemental Digital Content is Available in the Text.